Bully at work : what you can do to stop the hurt and reclaim your dignity on the job - Namie, Gary.; Namie, Ruth. (Naperville, Ill. : Sourcebooks, 2009)
In this updated edition of Bully at Work, based on an updated survey of workplace issues, the authors explore new grounds of bullying in the 21st century workplace.
pt. 1. The workplace bullying phenomenon: silent epidemic -- Bullying at work -- Understanding bullies -- Targethood : an undeserved burden -- The irreconcilable difference -- Witness paralysis -- Help from family and professionals -- Getting ready to confront -- pt. 2. After the assault, restoring the lost you -- Work trauma : understand the injuries done to you -- Assess the bully's impact -- Establish and protect personal boundaries -- Avoid unattainable standards -- Counter your inner critic -- Control destructive mind games -- Escape the trap of self-blame -- Satisfy your needs and wants -- Anger and shame : emotions of bullying -- pt. 3. What can one person do? -- Make yourself safe -- Facing the future -- pt. 4. Making employers responsible -- The world declares war on bullying -- America wakes up -- Appendix A : U.S. workplace bullying survey -- September 2007 -- Appendix B : Employer and co-worker response survey -- Labor Day 2008.
Includes bibliographical references (pages 323-326) and index.
Keywords: Bullying in the workplace; Bullying; Interprofessional Relations; Workplace; Business & economics -- Motivational; Business & economics -- Mentoring & Coaching; Bullying in the workplace; Electronic books